AUTOMATIC SOLAR-POWERED EMERGENCY LIGHTING AND POWER ISOLATION FOR FLOOD-AFFECTED HOMES - Azli, Shakira Azeehan; Mokhtar, Siti Musliha Ajmal; Bakar, Zahari Abu; Ismail, Nur Asfahani; Zin , Affida M (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2026)
Flood disasters are among the most frequent and disruptive natural hazards in Malaysia, often causing prolonged power outages that compromise the safety and visibility of residents in landed houses. Although emergency lighting and flood monitoring systems have been widely developed, few solutions integrate autonomous renewable power supply, automatic electrical isolation, and real-time IoT monitoring into a single household safety system for flood emergencies. This paper presents the development of Automatic Solar-Powered Emergency Lighting and Power Isolation for Flood-Affected Homes, an automated emergency backup lighting system designed to reduce electrical hazards and maintain emergency lighting during flood events. To ensure operational continuity during rising water levels, the system is intended for installation at elevated positions, such as rooftops or upper floors. The methodology involves an ESP32 microcontroller integrated with a suite of sensors, including water level, current, voltage, and temperature, to monitor environmental conditions and manage electrical safety. This project utilises a solar-harvesting mechanism to charge a 9V battery, ensuring a sustainable power supply for LED illumination in the event of a grid failure. System performance was validated through Wokwi simulation, where it successfully demonstrated real-time data visualisation via an LCD interface and the Blynk IoT platform. Results indicate that the system effectively triggers safety indicators, such as buzzers and emergency lighting, while automatically cutting off unsafe power lines to prevent electrical hazards. The proposed system offers a practical solution for improving household resilience by reducing electrical hazards and maintaining essential lighting during flood-induced power failures. Unlike existing flood monitoring systems that primarily provide notifications, the proposed system integrates solar-powered emergency lighting, automatic electrical power isolation, environmental sensing, and IoT-based monitoring within a single low-cost platform for residential flood protection.